Reversible Reductive Elimination in Aluminum(II) Dihydrides. (24th November 2020) - Falconer, Rosalyn L.; Nichol, Gary S.; Smolyar, Ivan V.; Cockroft, Scott L.; Cowley, Michael J.
Abstract: Oxidative addition and reductive elimination are defining reactions of transition‐metal organometallic chemistry. In main‐group chemistry, oxidative addition is now well‐established but reductive elimination reactions are not yet general in the same way. Herein, we report dihydrodialanes supported by amidophosphine ligands. The ligand serves as a stereochemical reporter for reversible reductive elimination/oxidative addition chemistry involving Al I and Al III intermediates. Abstract : Low‐oxidation‐state main‐group compounds exhibit rich oxidative addition chemistry. The same is not true for the reverse process, reductive elimination. Put together, the processes enable numerous catalytic cycles in transition‐metal chemistry. Here, using a stereoactive ligand as a reporter, it is revealed that Al II dihydrodialanes exhibit transition‐metal‐like reversible reductive elimination. Mes=2, 4, 6‐trimethylphenyl.